2020
DOI: 10.1109/tps.2020.2984156
|View full text |Cite
|
Sign up to set email alerts
|

Shaped Beams from Diamond Field-Emitter Array Cathodes

Abstract: Diamond field-emitter arrays (DFEAs) are arrays of diamond pyramids with exquisitely sharp tips and micrometerscale bases that produce high current densities. These arrays can be fabricated in arbitrary shapes, ranging from single tips to many millions of tips, so that they produce an inherently shaped electron beam. Each tip emits a modest current, but the large dense array can produce many Amps. We are investigating these cathodes for use in dielectric wakefield accelerators; however, they may also be applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…As an example of a transversely shaped distribution, a triangular array of pyramid emitters was deposited into a 1-mm equilateral triangle with ∼ 10 µm spacing on a cathode plug (Andrews et al, 2020), as shown in Fig. 10(a).…”
Section: Fe Based Shaped Transverse Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example of a transversely shaped distribution, a triangular array of pyramid emitters was deposited into a 1-mm equilateral triangle with ∼ 10 µm spacing on a cathode plug (Andrews et al, 2020), as shown in Fig. 10(a).…”
Section: Fe Based Shaped Transverse Distributionsmentioning
confidence: 99%
“…SEM image of rectangular array on a cathode plug (c) with diamond tips (inset), and its corresponding electron bunch image on a downstream screen showing a grid-shaped pattern (d). From(Andrews et al, 2020;Nichols et al, 2020).…”
mentioning
confidence: 99%